The Effect of Two Exercise Types in the 8 Week Exercise Training on the Physical Fitness of Elderly Women - Inhwa Yoo; Hyung-Min Yoon (Asian Society of Kinesiology, 2020)
OBJECTIVES The purpose of this study was to investigate the effect of two exercise types (Gyrokinesis exercise and Elastic band exercise) in the 8 week exercise training on the physical fitness of elderly women. METHODS The subjects of this study were 57 elderly women between 65 and 80 years old, who had no abnormality in the Physical Readiness Questionnaire (PAR-Q test) and were able to do physical activity on the orthopedic standpoints. The subjects were divided into three groups: Gyrokinesis Exercise Group (GKEG: n=19), Elastic Band Exercise Group (EBEG: n=20), and Control Group (CG: n=18). The subjects performed a Gyrokinesis Exercise in GKEG and an Elastic Band Exercise in EBEG for 50 minutes a day (10 minutes for warm-up, 30 minutes for main exercise, 10 minutes for cool-down), and 3 times a week for a total of 8 weeks. The subjects of CG did not participate in any particular exercise program but only everyday life. The dependent variables were Physical Fitness: Upper Muscular Endurance, 30-Second Arm Curl. Lower Flexibility, Dynamic Balance, Endurance. one-way ANOVA with repeated measurements was used to test the hypothesis in this study. A post hoc was conducted only when there was an interaction effect between groups and measurements. The difference of the post-test between groups were analyzed through Scheffe method after one-way ANOVA. The statistical significance level of this study was α=.05. RESULTS Gyrokinesis and Elastic Band Exercises were both effective on the physical fitness of elderly women: Upper Muscular Endurance, 30-Second Arm Curl, Lower Flexibility, Dynamic Balance, and Endurance. However, there were no differences in exercise effects after 8 week exercise training between the Gyrokinesis Exercise Group and the Elastic Band Exercise Group. CONCLUSIONS It is concluded that Gyrokinesis and Elastic Band exercise programs should be encouraged to improve physical fitness of elderly women and we need a follow-up study with longer term exercise training programs to find the differences in exercise effects between Gyrokinesis Exercise and Elastic Band Exercise.